Study on aerodynamic performance and wake characteristics of a floating offshore wind turbine under pitch motion - Fu, Shifeng; Li, Zheng; Zhu, Weijun; Han, Xingxing; Liang, Xiaoling; Yang, Hua; Shen, Wenzhong (Renewable energy, 2023)
The unsteady aerodynamic characteristics and interference effects of floating offshore wind turbine (FOWT) are mainly affected by the pitch motion of the ocean platform. Based on computational fluid dynamics (CFD) and advanced overset grid technology, the aerodynamic performance and wake characteristics of a fully configured wind turbine with rotating blades, nacelle , and tower are studied in this paper. The effects of the amplitude and frequency of pitch motion on the wind turbine aerodynamic loads and flow field are investigated herein in detail. The power and thrust between numerical simulation and experiment are compared. The results show that the grid and simulation parameters used in this study can accurately capture the aerodynamic characteristics and the flow field around wind turbines. The influence of the pitch amplitude and frequency on the performance of wind turbines is discussed. The complex flow interaction between the tip vortex, tower shedding vortex, and the turbulent wake was observed. The present results indicate that the pitch motion amplitude and frequency have a great influence on the power, thrust, and wake characteristics.